The development of anterior-posterior spinal curvature in children aged 7-12 years - Drzał-Grabiec Justyna; Snela Sławomir; Truszczyńska Aleksandra (Sciendo, 2016)
Study aim: Body posture changes depend on numerous factors. The purpose of this study was to assess the changes in posture in the sagittal plane of children aged 7-12 years.